Effect of Plasma and Alkaline Combination Treatment on Dyeing Properties of Pet Fabric and Mechanism Discussion - ELABID, Amel; Jing, ZHANG (Gezira Journal of Engineering and Applied Sciences, 2019)
Investigation of plasma and alkaline combination treatment of polyethylene terephthalate (PET) fabric and its application in dyeing with less energy consuming, less time and pollution, also the dyeing mechanism. It firstly explored the alkaline treatment of PET and textile properties at different conditions of treatments. This paper, studied a low alkaline treatment temperature and concentration were chosen to combine together with plasma treatment at different process. The topographical changes and chemical modification of the fabric surface were analyzed, using X-ray Photoelectron Spectroscopy (XPS). The XPS results showed that the plasma pre-treatment had introduced oxygen containing groups (O–C=O, C–O, and COOH) onto the fabric surface. Dyeability of the modified fabric was investigated by dyeing using disperse blue dye. The obtained results were compared with the high temperature dyeability of the untreated fabric. The result showed that a significant increase of K/S value (8.87) and % dye uptake (71.71) at dyeing temperature of 100 ° C with a combination of plasma and alkaline treatments compared with untreated, only plasma treated and only alkaline treated fabrics at dyeing temperature of 130 ° C. Thus, the oxygen/argon plasma-alkaline combination treatment of PET fabric can get better dyeing properties at low dyeing temperature of 100 ° C than that at 130 ° C, which means a lot of energy saving. Overall, plasma treatment has a great improvement effect with alkaline treatment to improve the dyeing properties of PET fabrics at low temperature.